2021
DOI: 10.3390/insects12020119
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Small Heat Shock Protein Genes (Hsp17.4 and Hs20.3) from Sitodiplosis mosellana, and Their Expression Regulation during Diapause

Abstract: Sitodiplosis mosellana, a periodic but devastating wheat pest that escapes temperature extremes in summer and winter by undergoing obligatory diapause. To determine the roles of small heat shock proteins (sHsps) in diapause of S. mosellana, we characterized two sHsp genes, SmHsp17.4 and SmHsp20.3, from this species. Both SmHsps contained the conserved α-crystallin domain and the carboxy-terminal I/VXI/V motif of the sHsp family. SmHsp17.4 had one intron while SmHsp20.3 had none. Quantitative PCR revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Acting independently of ATP, they are the first line of cell defense, preventing the irreversible denaturation of substrate proteins, especially when cells are stressed [ 18 ]. Small HSPs have been extensively studied in diapausing insects, including the fruit flies Drosophila triauraria and D. melanogaster [ 23 , 81 ], the flesh fly, S. crassipalpis [ 96 ], the corn stalk borer S. nonagrioides [ 70 ], the wheat midge S. mosellana [ 97 ], the butterfly Pieris melete [ 98 ], the leaf beetle Gastrophysa atrocyanea [ 99 ] and the silkworm B. mori [ 100 ]. The augmentation of sHSPs appears to be common during diapause in numerous species across different insect orders, including Lepidoptera, Diptera, Hymenoptera and Coleoptera, and can occur at different developmental stages (embryo, larva, pupa, adult) [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acting independently of ATP, they are the first line of cell defense, preventing the irreversible denaturation of substrate proteins, especially when cells are stressed [ 18 ]. Small HSPs have been extensively studied in diapausing insects, including the fruit flies Drosophila triauraria and D. melanogaster [ 23 , 81 ], the flesh fly, S. crassipalpis [ 96 ], the corn stalk borer S. nonagrioides [ 70 ], the wheat midge S. mosellana [ 97 ], the butterfly Pieris melete [ 98 ], the leaf beetle Gastrophysa atrocyanea [ 99 ] and the silkworm B. mori [ 100 ]. The augmentation of sHSPs appears to be common during diapause in numerous species across different insect orders, including Lepidoptera, Diptera, Hymenoptera and Coleoptera, and can occur at different developmental stages (embryo, larva, pupa, adult) [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many insects undergo a developmental process of seasonal dormancy termed "diapause", which offers an adaptive advantage to survive adverse environments and allows life cycle synchronization with suitable periods for growth, development, and reproduction [50]. Several studies have shown that insects' sHsps are associated with the diapause process and their implication during diapause might be quite different amongst different insect species [50,[55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic approach was used to investigate the proteins extracted from larvae of S. mosellana at different developmental stages, which include pre-diapause, over-summering diapause, Research Progress on Diapause in Flies (Diptera) DOI: http://dx.doi.org/10.5772/intechopen.106158 over-wintering diapause, and post-diapause. The results showed that two small Hsps play key roles in stress tolerance during diapause [62]. Proteins synthesized by pupal brains of the flesh fly S. crassipalpis were examined during diapause and non-diapause using pulse labeling and two-dimensional electrophoresis, and it was found that a cluster of about 15 brain proteins appears to be specific to diapausing pupae [63].…”
Section: Diapause-associated Changes In Proteinsmentioning
confidence: 99%